Why do so few low‐ and middle‐income children attend a grammar school? New evidence from the Millennium Cohort Study. (8th February 2019) - Jerrim, John; Sims, Sam
Abstract : Proponents argue that grammar schools enhance social mobility by allowing high‐attaining pupils to attend elite schools, no matter what their social background. However, disadvantaged pupils cannot benefit from grammar schools unless they gain access to them. In this article, we use rich cohort data to investigate the strength of, and reasons for, the socio‐economic gradient in grammar school entrance rates. Presenting new evidence for England and Northern Ireland, we find stark differences in grammar school attendance by family income. Although differences in prior academic attainment can partly explain these gaps, parental school preferences and private tuition also play an important role. Entrance to grammar school therefore depends on birth and wealth, as well as academic attainment.